College Academic Performance of Teacher Education Students in a State University of Northern Philippines - Pascua, Juanita B.; Navalta, Jane D.; Dela Cruz, Leila M.; Valderama, Julius S. (JPAIR Multidisciplinary Research, 2012)
The study determined the factors that influence the college academic performance of the respondents. This study used the descriptive and correlational survey methods of research with document scanning. It was found that gender and degree/course of the respondents were not significant factors in college academic performance; HS GPA was a significant factor that influences college academic performance; Admission Test Score in English and Science had no significant relationship on the college academic performance but in Mathematics, however, the higher the overall Admission Test Score, the higher is the college academic performance; male respondents did not differ in college academic performance when compared with their female counterparts and the BEED respondents did not differ in college academic performance when compared with their BSIE and BSED counterparts; and there was no significant difference between Admission Test Scores in General Information and Science when compared with their academic performance; however, when grouped according to admission test in English, those who obtained average and above average scores performed better in college than those who got failing and below average scores while in Mathematics, those who obtained average and above average scores performed better in college than those who failed and got below average scores.